Faulting and overburden and bedrock seismic velocities at Buchans and Gullbridge, Newfoundland, from seismic refraction measurements: applications to shallow geology and exploration - Wright, C. (Canadian Journal of Earth Sciences, 1996)
P-wave arrival times from seismic reflection surveys recorded at two mine sites in Newfoundland were used to estimate lateral variations in seismic velocity in uppermost bedrock. The abundant information on medium- to long-wavelength lateral variations in seismic velocity in bedrock is a by-product of refraction statics analyses, which has rarely been fully exploited to constrain shallow geological interpretation. Local minima in seismic velocity in bedrock are associated with faults, showing that subvertical features that do not produce observable reflections can also be mapped. Significant variations in seismic velocity also indicate variations in lithology or formation boundaries. Variations in overburden and weathering thicknesses are accurately defined at Gullbridge where the careful choice of shot–receiver configuration allows estimates of both lateral and vertical variations in the seismic velocities of glacial overburden. The information on overburden properties is of value in drift prospecting for minerals and in studies of Quaternary geology.